Study on the Effectiveness of the People Representative Council in Legislation of Regional Regulations - Pardomuan, Basrah; Adam, Adam; Kusmanto, Heri (Journal La Sociale, 2025)
This study aims to examine the effectiveness of the Regional People's Representative Council (DPRD) of Langkat Regency in regional regulation legislation (Perda) during the 2019-2024 period. The research method used is qualitative descriptive with data collection through in-depth interviews, direct observation, and document studies. The results of the study show that the Langkat Regency DPRD has ratified a number of Regional Regulations, both initiated by the DPRD itself and proposed by the executive. However, the effectiveness of the DPRD in legislation is still influenced by the quality of human resources, low public participation, dominance of executive roles, and political dynamics within the DPRD. The quality of human resources and the capacity of DPRD members are obstacles in formulating Regional Regulations that are responsive to the needs of the community. Community participation in the process of formulating the Regional Regulation is also still limited, so the aspirations of the community have not been fully accommodated. In addition, the dominance of the executive in the submission of the Regional Regulation reduces the initiative of the DPRD in making policies. Despite the challenges, opportunities to increase the effectiveness of the DPRD are still open through increasing human resource capacity and optimizing community participation. With this effort, it is hoped that the Langkat Regency DPRD can produce a higher quality Regional Regulation and support regional development.